Associations between causal attributions for obesity and long-term weight loss. Issue 2 (2nd April 2020) - Pearl, Rebecca L.; Wadden, Thomas A.; Chao, Ariana M.; Alamuddin, Naji; Berkowitz, Robert I.; Walsh, Olivia; Allison, Kelly C.; Tronieri, Jena Shaw
Abstract: Obesity is a complex disease caused by a wide array of behavioral, biological, and environmental factors. However, obesity is often attributed to oversimplified and stigmatizing causal factors such as laziness, lack of willpower, and failure to take personal responsibility for one's health. Understanding of the causal factors that contribute to obesity among people with obesity may affect their weight management efforts. The current study explored associations between causal attributions for obesity and long-term weight loss, as well as examined potential changes in attributions with weight reduction. The 16-item Causal Attributions for Obesity scale (rated 1-7) was administered to 178 patients seeking behavioral/pharmacological weight-loss treatment. Causal attributions and weight were assessed at baseline, after 14 weeks of a low-calorie diet, and again at weeks 24 and 52 of a subsequent randomized trial (i.e., 66 weeks total). Logistic and linear regression examined effects of baseline causal attribution ratings on weight loss. Higher baseline ratings of personal responsibility attributions predicted 38% reduced odds of achieving ≥10% weight loss at week 52 ( p  = 0.02). Causal attribution ratings did not change over time or correlate continuously with weight change. Thus, attributing obesity to a failure of personal responsibility may impair long-term weight management efforts for individuals seeking ≥10% weight loss. Targeted techniques are needed to reduce patients' stigmatizing beliefs about the causes of obesity.